Research on Application of Big Data Technique in Electricity Power Industry - Yunshan Zhao; Huanhuan Liu (Dianxin kexue)
With the rapid development of information technology, the ubiquitous sensor network, high-speed communication network, and the high performance distributed computing system have been commonly implemented. The massive data, which is generated anytime, with the mass storage, heterogeneous structure, and requiring on-time process, is bringing our society into the age of big data. The electricity big data includes the information of production, transportation, marketing, enterprise operation and management in the electricity power enterprise. Therefore, how to collect, transfer, store, and analyze the big data so as to conduct the production, and serve the electricity end users turns to an important research subject for the power industry. An overview was given about the features of the age of big data from three aspects: the definition, development trend, and the key technology of big data. Then, a summary of the research and typical application of the existing big data technology in the electric power industry was described. Finally, the challenges of big data technology in the future for the electric power information were concluded.